Further characterisation of the 'ileal brake' reflex in man–effect of ileal infusion of partial digests of fat, protein, and starch on jejunal motility and release of neurotensin, enteroglucagon, and peptide YY. Issue 8 (August 1988) - Spiller, R C; Trotman, I F; Adrian, T E; Bloom, S R; Misiewicz, J J; Silk, D B
Abstract : Previous studies have shown that ileal infusion of partially digested triglyceride inhibits jejunal motility. The partial digest used in those studies contained a mixture of glycerol, free fatty acid, mono-, di-, and triglycerides. In Part I of the present study we have separately infused emulsions containing either glycerol 3.1 g (n = 6), oleic acid 9.6 g (n = 6), triolein 10 g (n = 12), or medium chain triglycerides 10 g (n = 6) into the ileum and have recorded the effect this has on jejunal motility. Five further subjects received infusions of partial hydrolysates of corn starch 10 g and lactalbumin 7 g. Marked inhibition of jejunal pressure wave activity was seen after all three lipid infusions, per cent activity falling from a control of 37.7 (7.7) to 6.2 (2.1) and 22.4 (8.2)% 30 min after completing the oleic acid and triolein infusions respectively, and from a control value of 39.5 (4.1) to 17.7 (4.7) after MCTs (all p less than 0.05). No significant fall occurred after infusion of glycerol, protein or carbohydrate. All three lipid infusions raised plasma concentrations of neurotensin, enteroglucagon and peptide YY equally effectively, although only the rise in peptide YY correlated significantly with the inhibition of jejunal pressure wave activity (r = 0.80, n = 6, p less than 0.05). In Part II of this study six subjects received a 3 ml/min jejunal infusion of an isotonic carbohydrate saline solution followed after three hours by a similar infusion of a partial digest of lipid. During each infusion flow and transit time was measured by marker and dye dilution. Jejunal infusion of the carbohydrate-saline solution was associated with low jejunal flow, 4.7 (1.0) ml/min and a mean transit time through the 50 cm study segment of 36.5 (7.1) min. By contrast jejunal infusion of partially digested triglyceride was associated with a markedly increased flow, 9.0 (1.2) ml/min, a fall in mean transit time to 20.3 (2.6) min and significant rises in pancreaticobiliary secretions. Jejunal triglyceride also increased the incidence of prolonged high amplitude jejunal pressure waves in four of six subjects. These studies suggest that there are important differences in the jejunal response to ileal versus jejunal lipid. While long and median chain free fatty acids infused into the ileum exert an inhibitory effect on jejunal motility, when infused directly into the jejunum partially digested triglyceride accelerates transit, increases jejunal flow and subtly alters the pattern of jejunal contractions.